Computer Simulation - Cvetkovic, Dragan (IntechOpen, 2017)
The first chapter provides an overview of the development of a novel agent-based simulation model of socio-environmental innovation diffusion. The second chapter shows the study about rendering of colours with three rendering engines. The third and fourth chapters are devoted to modelling clothes at different levels. The fifth chapter describes the modelling of computer simulation in the optimization of bioprocess technology. Chapters 6 and 7 formulate a physical model of deformation of steel and idea of constructing a scientific workshop focused on high-temperature processes. Chapter 8 formulates surrogate models. Chapter 9 shows computer simulation of high-frequency electromagnetic fields. Chapter 10 proposes the modelling of the task allocation problem by the use of Petri Nets. Chapter 11 presents various scenarios whose ranking is done according to defined criteria and weight coefficients.